2021
DOI: 10.4049/jimmunol.2001317
|View full text |Cite
|
Sign up to set email alerts
|

STING Agonist Mitigates Experimental Autoimmune Encephalomyelitis by Stimulating Type I IFN–Dependent and –Independent Immune-Regulatory Pathways

Abstract: The cGAS–cyclic GMP–AMP (cGAMP)–stimulator of IFN genes (STING) pathway induces a powerful type I IFN (IFN-I) response and is a prime candidate for augmenting immunity in cancer immunotherapy and vaccines. IFN-I also has immune-regulatory functions manifested in several autoimmune diseases and is a first-line therapy for relapsing–remitting multiple sclerosis. However, it is only moderately effective and can induce adverse effects and neutralizing Abs in recipients. Targeting cGAMP in autoimmunity is unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…A previous study showed that IFN-I through the STING-mediated pathway promotes the level of IL-10 [ 62 , 63 ]. In contrast, the activation of bone marrow-derived macrophages (BMDM) via cGAS-STING signaling in an allergic encephalomyelitis (EAE) mouse model showed IL-10 production without requiring IFN-I [ 64 ]. Therefore, IL-10 production can also occur through several pathways, including TLR signaling, IFN-I, and nuclear factor kB (NF-kB) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that IFN-I through the STING-mediated pathway promotes the level of IL-10 [ 62 , 63 ]. In contrast, the activation of bone marrow-derived macrophages (BMDM) via cGAS-STING signaling in an allergic encephalomyelitis (EAE) mouse model showed IL-10 production without requiring IFN-I [ 64 ]. Therefore, IL-10 production can also occur through several pathways, including TLR signaling, IFN-I, and nuclear factor kB (NF-kB) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is mainly secreted by activated T-cells, which is an important anti-in ammatory cytokine [23]. It has been reported that STING agonist promoted IL-10 expression to relieve mice with experimental autoimmune encephalomyelitis [24]. This research indicated that STING agonist might synergize with Atezolizumab to exert anti-tumor effect by reducing in ammation via increasing IL-10 expression.…”
Section: Discussionmentioning
confidence: 91%
“…When phagocytosed by myeloid cells, mitochondrial DNA from SLE-derived red blood cells stimulated type I IFN production in a cGAS/STING-dependent manner (75). In contrast, delivery of DNA or cGAMP through microparticles offers protection against disease in animal models of experimental autoimmune encephalomyelitis and type 1 diabetes (76,77). These studies suggest that although endogenous DNA may be a contributing factor to the pathogenesis of certain autoimmune diseases, further studies are needed to better understand its specific role in autoimmunity and the pathways involved and to determine the exact sources of the endogenous DNA at play.…”
Section: Potential Role Of Intracellular Dna-sensing Pathways In Auto...mentioning
confidence: 99%